Evolving (dis)engagement: analyzing employees' responses to sustainability initiatives through causal loop diagrams - Bettker Vasconcelos, Carolina; Sanchez-Zeziaga, Ane; Henning, Klaus; van der Meer, Yvonne (Frontiers in Sustainability, 2025)
IntroductionThis study employed a systems thinking approach to explore the complex and dynamic interactions between sustainability initiatives, and employees' subsequent perceptions, attitudes, and behaviors. It aims to address limitations in existing literature, arising from methodological approaches that fail to capture the nuances in employees' responses, and a lack of knowledge integration.MethodsInsights from neo-institutional theory, sensemaking, and attribution theory were integrated with findings from 46 previous studies and 50 empirical qualitative data points though Causal Loop Diagrams (CLDs) to reveal feedback mechanisms and temporal dynamics that potentially shape employees' responses to sustainability initiatives.Results and discussionTwo main reinforcing feedback loops were identified: one supporting continued engagement and implementation of sustainability initiatives, and another hindering initiatives through negative perceptions. A balancing loop revealed how increasing employee knowledge, experience and scrutiny can lead to more critical perceptions over time. The analysis suggests that more symbolic sustainability initiatives can foster initial employee engagement and support for future sustainability implementation in the early stages of a sustainability journey. However, this initial positive momentum can be fragile and transition into a "vulnerability period", where initial enthusiasm may transition to frustration if perceived impacts do not meet employees' growing expectations. This potential progression follows a “Fixes that Fail” systems archetype.ConclusionIn this study, the use of CLDs provides a more temporally-bound and integrated understanding of employees' responses to sustainability initiatives. Therefore, this study challenges the simplistic dichotomy of positive versus negative effects of sustainability initiatives, revealing a more nuanced interplay between individual differences and organizational factors in shaping progressive employee (dis)engagement. Ultimately, the findings suggest that symbolic initiatives are not inherently bad, but sustaining employee engagement requires organizations to “walk their talk” by implementing consistent initiatives whose perceived impact can withstand increasing employee scrutiny.